2003
DOI: 10.1677/joe.0.1770337
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between three commercial kits for chromogranin A measurements

Abstract: Chromogranin (CgA) has been shown to be an excellent marker for neuroendocrine tumours. There are now three commercial assays on the market. We wanted to compare the usefulness of the different kits in a clinical situation. We have thus measured CgA in 77 patients and compared the results from the different methods. CgA was measured with three different commercial kits according to the recommendations from the manufacturers (CGA-RIA CT; CIS bio international, Gif-sur-Yvette cedex, France, DAKO Chromogranin A E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
134
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 20 publications
9
134
1
3
Order By: Relevance
“…pancreastatin) usually have lower sensitivity in detecting patients with NETs (Tatemoto et al 1986, O'Toole et al 2009, Vinik et al 2009). Commercial kits for determining CgA are available and measurement of CgA is routine in the management of NETs (Stridsberg et al 2003, O'Toole et al 2009). It should be noted, however, that there is a fair amount of variability between assays with sensitivities varying from 67 to 93% depending on which assay is used (Stridsberg et al 2003, O'Toole et al 2009).…”
Section: General Markers Chromograninsmentioning
confidence: 99%
See 1 more Smart Citation
“…pancreastatin) usually have lower sensitivity in detecting patients with NETs (Tatemoto et al 1986, O'Toole et al 2009, Vinik et al 2009). Commercial kits for determining CgA are available and measurement of CgA is routine in the management of NETs (Stridsberg et al 2003, O'Toole et al 2009). It should be noted, however, that there is a fair amount of variability between assays with sensitivities varying from 67 to 93% depending on which assay is used (Stridsberg et al 2003, O'Toole et al 2009).…”
Section: General Markers Chromograninsmentioning
confidence: 99%
“…Commercial kits for determining CgA are available and measurement of CgA is routine in the management of NETs (Stridsberg et al 2003, O'Toole et al 2009). It should be noted, however, that there is a fair amount of variability between assays with sensitivities varying from 67 to 93% depending on which assay is used (Stridsberg et al 2003, O'Toole et al 2009). In most NETs, CgA is more abundant than CgB and thus CgA is usually a better circulating tumour marker than is CgB (Fig.…”
Section: General Markers Chromograninsmentioning
confidence: 99%
“…Using the same cut-off point (18 U/l) as in our study, they received greater diagnostic sensitivity (85%) and specificity (96%) for the diagnosis of NET. With cut-off values from 17 to 34 U/l the estimated value of the diagnostic sensitivity of CgA from 79 to 92% [30,33] and specificity from 83 to 91% [22,30,33] was obtained in various other studies.…”
Section: Discussionmentioning
confidence: 92%
“…Intra-assay coefficients of variation were 4.5, 3.8 and 8.5% for the following ranges 5-10, 15-25 and 250-450 U/l, respectively (Zatelli et al, 2007). The three most commonly available employed assays for CgA measurement, has been compared in a group of NET patients and has been found that sensitivities vary between 67 and 93%, while specificities were 1 to 85% for all three (Stridsberg et al, 2003). A recent multicenter prospective comparison between two methods, immunoradiometric and ELISA, found a 36% clinical discordance rate.…”
Section: Chromogranin: Laboratory Testmentioning
confidence: 99%